Comparative Analysis of Financial Flows in the Healthcare Systems of Germany, Austria and Czechia: Opportunities for Savings and Assessing the Tax-Like Nature of Health Insurance Contributions - Mini, Patrick (ACTA VŠFS)
Background: Healthcare and pension expenditures represent significant budgetary commitments in OECD countries, with considerable variation in spending levels influenced by factors such as demographic structures, healthcare system models, and the role of private insurance. Germany, Austria, and Czechia exemplify diverse approaches to universal healthcare, reflecting unique socio-economic and policy contexts. Objective: This study aims to compare the financial flows and spending efficiencies of healthcare systems in Germany, Austria and Czechia to identify opportunities for savings and policy innovations. Methods: A comparative analysis of secondary data from OECD reports and academic literature was conducted, examining key metrics such as public and private expenditure, health insurance contributions, and administrative costs. Results: The analysis reveals that while Germany’s dual public-private insurance system ensures comprehensive coverage, it faces challenges in integrating care services. Austria’s regionally managed system benefits from robust public funding but struggles with administrative complexity. Czechia’s centralised financing model supports equitable access but requires improved resource allocation and efficiency. Across all systems, health insurance contributions exhibit tax-like characteristics, with significant implications for public policy and perception. Recommendations: Policymakers should consider measures such as integrating care services in Germany, streamlining administrative processes in Austria, and refining fund redistribution mechanisms in Czechia. Leveraging digital health technologies and fostering transparency in healthcare financing are critical for achieving systemic savings and equity. Practical relevance/social implications: This study highlights the importance of tailored financial reforms to address demographic shifts and rising healthcare costs. Its findings provide actionable insights for policymakers aiming to balance equity and efficiency in healthcare financing while ensuring public trust and sustainability. Originality/value: By dissecting the healthcare financial flows in Germany, Austria, and Czechia, this study offers a nuanced understanding of their systems' dynamics and identifies opportunities for cross-border learning to inform global healthcare policy reform.